The influence of strategic leadership, transformational leadership and visionary leadership on performance at the naval academy mediated by decision making - Denih Hendrata; Willy Arofah; Dedi S.Martadisastra (Institute of Computer Science (IOCS), 2023)
This study aims to determine and explain the effect of Strategic Leadearship, Transformational Leadearship and Visionary Leadearship on Decision Making mediated by the Performance of the Naval Academy. The sample used in this study was 146 respondents who were taken using purposive sampling and data collection methods using questionnaires or online questionnaires. The use of PLS ​​SEM was carried out by considering the limited number of samples used which resulted in the level of difficulty of the respondents used in this study. The population in this study is the Academic Community of the Naval Academy consisting of lecturers, educational staff. The results of this research showed that Strategic Leadearship, Transformational Leadearship and Visionary Leadearship have a positive effect on Performance in realizing Navy Officers who are ready to fight. Strategic Leadearship, Visionary Leadearship and Performance have a positive effect on Decision Making in realizing war-ready Navy Officers, while Strategic Leadearship has no effect. Strategic Leadearship and Visionary Leadearship have a positive effect on Transformational Leadearship in realizing Navy Officers who are ready to fight..